The relationship between health-related variables and increases in smoking among recently diagnosed HIV+ people who inject drugs in Vietnam. (August 2019) - Chockalingam, L.; Pence, B.; Frangakis, C.E.; Ha, T.V.; Latkin, C.A.; Sripaipan, T.; Quan, V.M.; Go, V.F.
Abstract: Background: In Vietnam tobacco smoking is prevalent among people living with HIV (PLHIV) and causes excess mortality in this population. Injection drug use is a driver of HIV infections in Vietnam. Changes in HIV disease state may correlate to changes in smoking among PLHIV. This study investigates the relationship between increases in smoking and health-related variables among recently diagnosed HIV+ people who inject drugs (PWID) in Vietnam. Methods: We analyzed longitudinal data from 323 recently diagnosed HIV+ PWID in a randomized controlled trial from 2009 to 2013 in Thai Nguyen province, Vietnam. The outcome was an increase of >one cigarette/day from baseline visit cigarette smoking. A generalized estimating equation for repeated measures was used to estimate bivariable and multivariable associations between participant characteristics and smoking increases. We collected qualitative data to enhance our understanding of quantitative results, from 16 HIV+ PWID who smoke. Results: Ninety three point 5% of participants reported some smoking at baseline. Smoking fewer cigarettes, higher health related quality of life (QOL), and higher CD4 counts were predictive of increases in smoking at future visits in a multivariable model. Qualitative data showed smoking increases were tied to improved perceived health, and counseling during respiratory illnesses may increase intention to quit. Conclusion: HIV+ PWID in Vietnam smoke at a very high rate. Increases in their smoking are correlated to increases in heath-related QOL, and increases in perceptions of health. Any tobacco-use intervention should account for internal tobacco use triggers faced by HIV+ PWID. Highlights: 93.5% of HIV+PWID in Thai Nguyen province, Vietnam reported smoking at baseline. Higher CD4 counts and higher quality of life predicted increases in smoking. Qualitative participants voiced improved perceived health led to smoking increases.